2002
DOI: 10.1007/s11661-002-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the hydrogen desorption process from ferrite, pearlite, and graphite by secondary ion mass spectrometry

Abstract: The distribution and desorption processes of hydrogen and deuterium have been visualized by secondary ion mass spectrometry (SIMS). The present article deals with four principal points: (1) visualizing the hydrogen distribution, (2) visualizing the hydrogen desorption process from each metallurgical microstructure under various holding times at 25 ЊC, (3) visualizing the hydrogen desorption process during heating, and (4) determining the correspondence between desorption profiles and desorption sites. A sphero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…25,26) Concerning steels samples, dynamic SIMS has been shown to be an effective method for detecting deuterium or hydrogen in different steels. [27][28][29][30][31][32] These results showed that deuterium or hydrogen is enriched in specific microstructures, although this enrichment depends on the species of steel. The dynamic SIMS has also been applied to observe the distribution of light elements such as boron and nitrogen in steels.…”
Section: Micro-portion Image Analysis Of Light Elements In Fe-cr Basementioning
confidence: 94%
“…25,26) Concerning steels samples, dynamic SIMS has been shown to be an effective method for detecting deuterium or hydrogen in different steels. [27][28][29][30][31][32] These results showed that deuterium or hydrogen is enriched in specific microstructures, although this enrichment depends on the species of steel. The dynamic SIMS has also been applied to observe the distribution of light elements such as boron and nitrogen in steels.…”
Section: Micro-portion Image Analysis Of Light Elements In Fe-cr Basementioning
confidence: 94%
“…The results indicate that most of hydrogen was stored in graphite and pearlite. Takai et al 5 showed that hydrogen was mainly segregated at graphite-ferrite interface and pearlite. Ogi et al 6 concluded that the reason why ferritic spheroidal graphite cast iron can store more hydrogen than ferritic steel is because graphite/matrix interface has a great capacity to store hydrogen.…”
Section: µM Ferritementioning
confidence: 99%
“…Hiroki SHODA, 1) Hiroshi SUZUKI, 2),3) Kenichi TAKAI 2), 3) and Yukito HAGIHARA 2) 1) Formerly Graduate Student, Sophia University. Now at NSK Ltd., 7-1 Kioi-cho, Chiyoda-ku, Tokyo 102-8554 Japan.…”
Section: Hydrogen Desorption Behavior Of Pure Iron and Inconel 625 Dumentioning
confidence: 99%
“…The trapping sites of this weakly trapped state are dislocations, vacancies, grain boundaries, cementite interfaces, and solid solution hydrogen in the lattice. [1][2][3][4] However, there is little agreement about the effects of trapping sites and how they cause hydrogen embrittlement. [5][6][7][8] The role of weakly trapped hydrogen or solid solution hydrogen diffusive at room temperature has been examined for Inconel 625 and pure iron.…”
Section: Introductionmentioning
confidence: 99%